Analisis Teknik Penerjemahan Humor Verbal dalam Takarir Film 8 Rue de l’Humanité: Analisis Teknik Penerjemahan Humor Verbal dalam Teks Terjemahan Film 8 Rue de l’Humanité - Raisya Tiara Nurradyarahma; Iim Siti Karimah; Farida Amalia (ELOQUENCE : Journal of Foreign Language, 2026)
Background: The growth of streaming platforms has advanced audiovisual translation;  however, humor transfer in films remains challenging due to linguistic and cultural context. Purpose: This study examines the subtitling of verbal humor in the French comedy film 8 Rue de l’Humanité (2021) into Indonesian to analyze how humor source characteristics influence translation technique selection. Method: A descriptive qualitative design using qualitative content analysis was employed, with the researcher serving as the primary instrument. The data consisted of the 125-minute French film 8 Rue de l’Humanité (2021) and its Indonesian Netflix subtitles. All subtitle utterances were screened, and those identified as verbal humor based on Shade’s classification were included in the analysis. Data were collected through document analysis using note-taking techniques and analyzed using the Miles and Huberman interactive model, integrating Shade’s verbal humor classification, Molina and Albir’s translation techniques, and Raphaelson-West’s humor sources. Analytical credibility was ensured through supervisory review and theory-based data cards that served as an audit trail. Results and Discussion: The analysis identified 40 instances of verbal humor in 8 Rue de l’Humanité (2021), dominated by irony, wit, and sarcasm, each occurring 10 times (25.0%). Six translation techniques were identified, with literal translation (42.5%) and modulation (27.5%) being the most frequent. The findings indicate that the selection of translation techniques is not determined by humor types but is instead influenced by the underlying characteristics of humor sources, whether universal, linguistic, or cultural. This study shows that humor source characteristics appear to influence translators’ decisions to preserve or reconstruct humorous effects in the target language. Conclusions and Implications: The study concludes that verbal humor transfer in subtitling does not rely on fixed techniques based on humor types. Instead, technique selection is adapted to humor source characteristics and the medium's spatial and temporal constraints. Future research should expand the corpus and examine audience acceptability.